The Effects of ICT on Environment Quality: The Role of Green Technological Innovation in Asian Developing Countries - Tahsin, Johora (Asian Journal of Economic Modelling, 2022)
To address the existing environmental challenges, the contributions of ICT and green technological innovation have gained considerable scholarly attention in recent decades. Therefore, this study investigates the effects of ICT penetration including green technological innovation on environmental quality in selected Asian developing countries, using data spanning the period 1990-2018. The long-run relationships among the variables are confirmed using panel ARDL and robust least squares techniques. The results suggest that environmental pollution diminishes after a threshold level of ICT development is attained. However, a significantly decreasing influence of green technological innovation is found on carbon emissions, leading to increased energy efficiency by promoting carbon-peaking and carbon neutrality goals. Furthermore, a bidirectional causality running from carbon emissions to ICT penetration and green technological innovation is affirmed by the Dumitrescu-Hurlin causality test. Therefore, more sound fiscal incentives must be implemented to further strengthen the efficient use of ICT products along with green technological innovation.